Access to care for adolescents seeking weight loss surgery. (19th September 2014) - Inge, Thomas H.; Boyce, Tawny W.; Lee, Margaret; Kollar, Linda; Jenkins, Todd M.; Brandt, Mary L.; Helmrath, Michael; Xanthakos, Stavra A.; Zeller, Meg H.; Harmon, Carroll M.; Courcoulas, Anita; Michalsky, Marc P.
<x xml:space="preserve">Abstract</x> Objective Adolescents seeking weight loss surgery (WLS) frequently encounter obstacles obtaining treatment authorization from insurance carriers. This study identified factors influencing authorization for adolescents with clinical indications for WLS. Methods A retrospective review was conducted for adolescents with clinical indications for WLS at five adolescent centers. This cohort represented a consecutive series of adolescents with insurance benefits for WLS for whom insurance authorization was sought between 2009 and 2011. Outcomes included number and timing of insurance authorizations for surgery, denials, and appeals. Results Records from 57 adolescents (74% female; mean age 16 (range: 12‐17) years; mean BMI 51.3 kg/m2) were reviewed. Of these, only 47% were approved with the original request. Eighty percent of those denied were approved on appeal, while 11% never obtained authorization for surgery. Age less than 18 years and proposed procedure were the most common reasons for denial. Conclusions Less than half of adolescents with clinical indications for surgery received approval for the procedure on the first request. The appeal process typically resulted in overturning of denials, so that surgical care could be delivered.